Art-based Pedagogical Interventions: Mitigating Second Language Anxiety among University Undergraduates in Southwest, Nigeria - Otunaiya, Ayodele Oluseyi; Eziamaka, Ezenandu Patricia; Stewart, Ashley (NIU Journal of Educational Research; Vol 12 No 2 (2026): NIU Journal of Educational Research, Vol. 12, No. 2, June 2026DO - 10.58709/niujed.v12i2.2592, 2026)
Second language anxiety negatively affects undergraduate students’ confidence, participation, and communicative competence in language classrooms. This study examined the effectiveness of art-based pedagogical interventions in reducing second language anxiety among undergraduates in the University of Lagos, Lagos State University, and Tai Solarin University of Education, Nigeria. A mixed-methods design was adopted, involving 180 purposively selected students identified through classroom observation and the Foreign Language Classroom Anxiety Scale (FLCAS). The twelve-week intervention integrated drama, storytelling, music, visual arts, and collaborative creative activities into second language instruction. Quantitative data were analyzed using descriptive statistics and t-test analysis, while qualitative responses were analyzed thematically. Findings revealed that art-based pedagogical interventions significantly reduced communication apprehension and improved students’ confidence, participation, and motivation toward second language learning. The study concludes that arts-integrated instructional strategies create supportive learning environments that enhance language acquisition and reduce anxiety among university undergraduates. It therefore recommends the integration of creative arts approaches into university language teaching and curriculum design. Keywords: Art-based Pedagogy, Second Language Anxiety, Language Learning, University Undergraduates, Nigeria.